Interaction between Maternal Obesity and Bishop Score in Predicting Successful Induction of Labor in Term, Nulliparous Patients - Zelig, Craig M.; Nichols, Shannon Flood; Dolinsky, Brad M.; Hecht, Maximilian W.; Napolitano, Peter G. (American Journal of Perinatology, 2013)
Objective Determine the Bishop score most predictive of induction of labor (IOL) success for different maternal weight groups.Study Design Retrospective cohort study. Prospectively collected database utilized to determine the optimum Bishop score within each prepregnancy body mass index (BMI) category of term, nulliparous patients undergoing IOL.Results For the total group (n = 696), Bishop score ≥5 was most predictive of success (75% versus 56%, p < 0.0001). Within each BMI category, Bishop score ≥5 remained most predictive: normal weight (79% versus 64%, p < 0.01); overweight (72% versus 58%, p = 0.03); and obese (73% versus 45%, p < 0.0001). Overall, nonobese patients had more success than obese patients (70% versus 59%, p < 0.01). The nonobese group had more success than the obese group when the Bishop score was <3 (57% versus 39%, p < 0.05) but not when it was ≥3 (72% versus 65%, p = 0.1). Also, there was a higher fraction of patients with Bishop score <3 in the obese group compared with the nonobese group (25% versus 14%, p < 0.001).Conclusion The optimum Bishop score for predicting successful IOL in nulliparous patients was 5 regardless of BMI class. The higher IOL failure rate observed in obese women was associated with lower starting Bishop scores and was compounded by higher failure rates in obese women with Bishop scores <3.
Keywords: BMI; Bishop; induction; nulliparous